Penerapan Metode Pembelajaran SQ4R untuk Meningkatkan Keterampilan Membaca Narrative Text - Karmila, Karmila (Universitas Muhammadiyah Magelang, 2019)
This study aims to find out how SQ4R strategy improves students’ reading skills of Narrative Text. The subjects are 36 students of X IPS 3. It uses CAR design which is carried out in 2 cycles. The data collection is conducted through classroom observation and test. The results showed that there is a match between the learning of Narrative Text Reading and the application of the SQ4R strategy. Students look enthusiastic about learning activities. Overall, the use of the